The effects of substrate morphology by regulating pseudopods formation on cell directional alignment and migration. (1st December 2021) - Zou, Jing; Jin, Kun; Chen, Tongsheng; Li, Xinlei
Abstract: When cells are cultured on the micro- or nano- structure substrate, filamentous pseudopods are formed at specific locations due to the effects of substrate morphology and local membrane curvature, which provides a powerful method to guide cell migration and neurite orientation. However, it is unclear the effects of substrate surface morphology and initial cell membrane on pseudopod formation and growth. Here, we present a quantitative thermodynamic model to investigate the difficulty of pseudopod formation. Based on the established model, we studied the effects of substrate morphology and the curvature of the initial cell membrane on filamentous pseudopods formation by analyzing the magnitude of an average driving force. We find that the pseudopod-substrate adhesion and the larger curvature radius of the initial cell membrane can facilitate filamentous pseudopods formation due to the smaller minimum resistance energy. Furthermore, our theoretical results seem to show a broad agreement with experimental observations, which implies that these studies would provide useful guidance to control the pseudopods formation on substrate for biomedical applications.